Pengaruh Model Pembelajaran Cognitive Academic Language Learning Approach Terhadap Minat Membaca Cerita Pendek di Kelas V SD - Setiartin, Titin; Rachman, Ichsan Fauzi; Maryani, Sri (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2025)
This research explains and explains the application of the Cognitive Academic Language Learning Approach (CALLA) learning model in appreciative reading learning in fifth-grade elementary school. The research uses experiments using quasi-experimental methods. The research controls one variable in the form of matching. Randomized Pretest-Posttest Comparison Group Design, research design using a non-equivalent pre-test and post-test design using the Kolmogorov Smirnov Test. T-test value (calculated t) of two paired samples for the Experiment Class variable (All classes) with the Control Class variable (Karanganyar I). If Sig. (2-tailed) < 0.05, the Sig value is obtained. (2-tailed) = 0.431, meaning the two samples are significantly different. The results of the research show that the CALLA model has a positive effect on increasing the metacognitive, cognitive, and social/affective competencies of 5th-grade elementary school students. The two variables are significantly different through the self-evaluation test. From the two paired sample t-test calculations for the Experiment Class variable (All classes) and the Control Class variable (Karanganyar I), the Sig value was obtained. (2-tailed) = 0.016, meaning the two samples are significantly different. The CALLA learning model is effective in improving the ability to read short stories in reading learning in fifth-grade elementary school.Abstrak Penelitian ini menjelaskan, dan memaparkan penerapan model pembelajaran Cognitive Academic Language Learning Approach (CALLA) dalam pembelajaran membaca apresiatif di kelas V SD. Penelitian menggunakan eksperimen dengan menggunakan metode eksperimen kuasi. Penelitian mengontrol satu variabel  dalam bentuk matching. Desain Kelompok Pembanding Prates-Pascates Beracak, desain penelitian menggunakan desain nonekuivalen prates dan pascates dengan menggunakan Kolmogorov Smirnov Test. Nilai Uji-t (t hitung) dua sampel berpasangan untuk variabel Kelas Eksperimen (Seluruh kelas) dengan variabel Kelas Kontrol (Karanganyar I). Jika Sig. (2-tailed) < 0,05 diperoleh hasil nilai Sig. (2-tailed) = 0,431, berarti kedua sampel tersebut berbeda secara signifikan. Hasil penelitian menunjukkan bahwa model CALLA berpengaruh positif terhadap peningkatan kompetensi metakognitif, kognitif, dan sosial/afektif siswa kelas kelas 5 SD. Secara signifikan kedua variabel berbeda melalui tes evaluasi diri. Dari perhitungan Uji-t dua sampel berpasangan untuk variabel Kelas Eksperimen (Seluruh kelas) dengan variabel Kelas Kontrol (Karanganyar I) diperoleh hasil nilai Sig. (2-tailed) = 0,016, berarti kedua sampel tersebut berbeda secara signifikan. Model pembelajaran CALLA efektif meningkatkan kemampuan membaca cerita pendek dalam pembelajaran membaca di kelas V SD.